Focus in Atlantic languages - (:unkn) unknown (My University, 2010)
This paper presents an overview of the formal markings characteristic of focus in Atlantic languages and reflection on some problematic uses of focused forms. A common (but not universal) feature of these languages is the use of verb morphology (in various ways) to express focus. What is most remarkable in several Atlantic languages (and apparently specific to this group) is that (1) verb forms indicate the syntactic status of the focused constituent; (2) these verb forms often merge focus, aspect, and voice features. This organization of the verb system has consequences for the range of uses of focused forms, in particular, for verb focus which is often used to express a mere statement in the case of verbs expressing a quality. These uses are accounted for through a renewed definition of the focused sentence as a "split assertion" involving a temporal presupposition and a qualitative designation.
Keywords: African Research